The Effect of Career Development and Recognition Systems on Employee Retention at PT Onedoor in Central Jakarta - Suryanto Sosrowidigdo (Sean Institute, 2026)
This study aims to analyze the effect of Career Development and Recognition System on Employee Retention at PT Onedoor in the Central Jakarta region. The increasing employee turnover indicates weaknesses in the implementation of career development and recognition systems. This research employs a quantitative approach using a saturated sampling technique with a total of 30 employees. Data were analyzed using multiple linear regression with SPSS. The results show that Career Development (sig. 0.032 < 0.05) and Recognition System (sig. 0.008 < 0.05) have a positive and significant effect on Employee Retention. Simultaneously, both variables also have a significant effect, as indicated by an F-value of 22.938 with a significance level of 0.000. The Adjusted R² value of 0.602 indicates that 60.2% of the variation in employee retention is explained by Career Development and Recognition System. Overall, this study confirms that clear career paths, development opportunities, and fair recognition systems play an important role in enhancing employee retention. Therefore, companies need to strengthen these aspects to maintain employee loyalty and workforce sustainability.